PENGUATAN PERAN KELUARGA DALAM PEMBENTUKAN KEPRIBADIAN ANAK MELALUI SEMINAR DAN PENDAMPINGAN MASALAH KELUARGA - Budi Lazarusli; Sri Lestari; Gufron Abdullah; Rahmat Sudrajat; Oktaviani Adhi Suciptaningsih (Universitas PGRI Semarang, 2014)
IbM strengthening the role of the family in shaping the personality of children through seminars and mentoring family problems done in the Village Rejosari Eastern District of Semarang Semarang City. The goal is to equip every individual in the community to understand the role of each in family life and society in order to create a harmonious life. The method used is to provide education in the form of seminars and mentoring the problems faced by the family. Participants are Rejosari village community includes parents, teens, men and women. The seminar took place on February 23, 2014, while assisting held in March 2014 in a week. Based on the results of quality improvement activities seemed relationships between family members with completion problems during mentoring activities.Keywords: Role of Family, Child Personality Formation, Family Issues